Different aqueous extracts of plants in soil treatment for Meloidogyne javanica control - Martins Marcondes, Mariana; Dallemole-Giaretta, Rosangela; Martins Marcondes, Marielle; Girotto Martins Ferreira, Silvana; Márcia Duarte Rios Faria, Cacilda (Revista de Ciências Agroveterinárias, 2015)
The objective of this study was to evaluate the effect of aqueous extracts of Baccharis trimera, Plantago sp., Verbena officinalis and Arctium lappa on the M. javanica control in the greenhouse. The experiment was performed in plastic pots containing a soil mixture and sand 2:1 (volume: volume), it was infested with 4.000 eggs of Meloidogyne javanica and 200 mL of the respective aqueous extract was added. After seven days a tomato seedling was transplanted in each pot. The evaluations of the number of galls and eggs of the nematode by root system were performed after 50 days of transplanting the seedlings. The data was subjected to analysis of variance and the means were compared by Duncan test at 5% probability. None of the tested treatments reduced the number of galls and eggs of M. javanica per root system.